Effectiveness of yoga for major depressive disorder: A systematic review and meta-analysis - Wu, Yufei; Yan, Danni; Yang, Jianli (Frontiers in Psychiatry, 2023)
Objective Major depressive disorder (MDD) has a relapse rate that cannot be ignored and places a tremendous burden on the patient in the prevention and treatment process. Yoga, a combination of physical and mental exercises, is effective and acceptable for the adjunctive treatment of MDD. This study aimed to explore further the evidence of yoga’s efficacy for patients with MDD. Methods PubMed, Embase, Cochrane library, PsycINFO, SinoMed, CNKI, Wanfang, and VIP databases from their inception to 13 October 2022 were searched by a pre-defined search strategy. RCTs of patients with MDD who met diagnostic criteria for yoga treatment were included. RoB2.0 was used to evaluate the quality of the literature. Improvement in depressive symptoms was assessed by the Beck Depression Inventory (BDI), Hamilton Depression Rating Scale (HAMD), or other scales were used as primary outcome indicators, and improvement in anxiety was assessed by the Hamilton Anxiety Scale (HAMA) and State–Trait Anxiety Inventory (STAI) scale as secondary outcome indicators. RR and Cohen’s d at 95% CI were used as effect size estimates, and Q and I2 were used to evaluate the size of heterogeneity, with a p-value less than 0.05 indicating statistical significance. Results Thirty-four RCT studies, including 1,269 patients in the treatment group and 1,072 patients in the control group, 48.4% of whom were women, were included in the study. Compared to the control group, the BDI-II results yielded a moderate effect of yoga on the improvement of depressive symptoms (Cohen’s d = −0.60; 95% CI: −1.00 to −0.21; p < 0.01), the HAMD results yielded a moderate improvement of yoga on the severity of depressive symptoms (Cohen’s d = −0.64; 95% CI: −0.98 to −0.30; p < 0.01), and the STAI results can be concluded that yoga had a negligible effect on the improvement of the level of anxiety (Cohen’s d = −0.26; 95% CI: −0.48 to −0.04; p = 0.02). No adverse events occurred in the yoga group during the treatment. Conclusion Yoga can improve depressive symptoms and anxiety in patients with MDD and has a safe and wide patient acceptance. Systematic review registration [https://www.crd.york.ac.uk/prospero/], identifier [PROSPERO, CRD42022373282].